KOMPOS ORGANIK DENGAN PEROMBAK AGRI SIMBA DAN PENGARUHNYA TERHADAP PERAKARAN KACANG TANAH (Arachis hipogaea L.) - Saiful Ridlo (The East Java Biological Society, 2004)
The dried rice stalks and banana stem are waste product after their harvesting but have potential as organic compost. Organic compost fertilizer treatment has a purpose to give nutrient for growth media until the root had enough and grow well. In this study, a peanuts root of two cultivars, kelinci and gajah, were grew in soil growth media which enrich an organic compost fertilizer, i.e. dried rice stalks, banana stem and mix of both composting with Agri Simba as starter, would be compared with control to look the kinds of growth media, cultivars and their interaction affect on rooting. The method used in this study was on experiment with on experimental design called completely randomized design. Each unit of the treatment tested four times. Many parameters would be studied in this case: length of the primary root, sum of live root apical, sum of nodules. They analyzed by two ways ANOVA test. Anatomical structure was analyzed by descriptive method. Harvesting of the cell have done 8th and 20th day after planting. The result of this study showed that organic composts have variation content of the N, P, and K on three kind of compost, certainly. The growth media treatment affected significantly (p < 0.05) in peanut rooting at less on root length and on sum of live root apical in early growth phase and sum of nodules in secondary growth. The cultivars treatment affected significantly (p < 0,05) on peanut rooting at less on sum of live root apical but not (p > 0.05) on root length and sum of nodules. Their interaction treatment not affected (p > 0.05) on rooting parameter observed. The treatments may affect on anatomical structure.